Bile acids destabilise HIF-1a and promote anti-tumour phenotypes in cancer cell models. - Phelan, J.; Reen, F.; Dunphy, N.; O'Connor, R.; O'Gara, Fergal (2016)
BACKGROUND: The role of the microbiome has become synonymous with human health and disease. Bile acids, as essential components of the microbiome, have gained sustained credibility as potential modulators of cancer progression in several disease models. At physiological concentrations, bile acids appear to influence cancer phenotypes, although conflicting data surrounds their precise physiological mechanism of action. Previously, we demonstrated bile acids destabilised the HIF-1a subunit of the Hypoxic-Inducible Factor-1 (HIF-1) transcription factor. HIF-1 overexpression is an early biomarker of tumour metastasis and is associated with tumour resistance to conventional therapies, and poor prognosis in a range of different cancers. METHODS: Here we investigated the effects of bile acids on the cancer growth and migratory potential of cell lines where HIF-1a is known to be active under hypoxic conditions. HIF-1a status was investigated in A-549 lung, DU-145 prostate and MCF-7 breast cancer cell lines exposed to bile acids (CDCA and DCA). Cell adhesion, invasion, migration was assessed in DU-145 cells while clonogenic growth was assessed in all cell lines. RESULTS: Intracellular HIF-1a was destabilised in the presence of bile acids in all cell lines tested. Bile acids were not cytotoxic but exhibited greatly reduced clonogenic potential in two out of three cell lines. In the migratory prostate cancer cell line DU-145, bile acids impaired cell adhesion, migration and invasion. CDCA and DCA destabilised HIF-1a in all cells and significantly suppressed key cancer progression associated phenotypes; clonogenic growth, invasion and migration in DU-145 cells. CONCLUSIONS: These findings suggest previously unobserved roles for bile acids as physiologically relevant molecules targeting hypoxic tumour progression.